The rise of Confucian ritualism in late imperial China ethics, classics, and lineage discourse - Chow, Kai-wing 1951- (Stanford Univ. Press, 1994)
This pathbreaking work argues that the major intellectual trend in China from the seventeenth through the early nineteenth century was Confucian ritualism as expressed in ethics, classical learning, and discourse on lineage. The conquest of China by the Manchus and the establishment of the Ching dynasty in the mid-seventeenth century provoked both political and identity crises for Chinese intellectuals. As a result, they returned to the classical heritage in an intensified search for pure Confucian doctrine and a ritualist expression of cultural identity under alien rule. Through the performance of rites, especially those concerned with family and lineage, the early Ching scholars believed they could cultivate Confucian virtues and rebuild a social order broadly based on kinship organization